ITU-UUM Visits to ISITI-UNIMAS - Universiti Malaysia Sarawak, Institute of Social Informatics and Technological Innovations (Universiti Malaysia Sarawak, (UNIMAS), 2014)
The Institute of Social Informatics and Technological Innovations (ISITI) hosted a seminar by Dr. Azizi Ab Aziz, Deputy Director from the International Telecommunication Union– Universiti Utara Malaysia (ITU-​UUM) Asia Pacific Center of Excellence for Rural ICT Development.